Expression Profile Analysis to Identify Circular RNA Expression Signatures in the Prolificacy Trait of Yunshang Black Goat Pituitary in the Estrus Cycle - Liu, Yufang; Wang, Peng; Zhou, Zuyang; He, Xiaoyun; Tao, Lin; Jiang, Yanting; Lan, Rong; Hong, Qionghua; Chu, Mingxing (Frontiers in Genetics, 2022)
The pituitary gland is an important organ. It is a complex area of the brain involved in endocrine function and reproductive regulation. However, the function of the pituitary in goat reproduction is still unclear. Herein, RNA sequencing was used to explore the expression patterns of circle RNAs (circRNAs) in the pituitary of Yunshang black goats during the various oestrus phases. Then, the host genes of the circRNAs were predicted, and a competing endogenous RNA (ceRNA) network was constructed. The results showed a total of 6705 circRNAs in the pituitary of Yunshang black goats, among which 388 differentially expressed (DE) circRNAs (214 were upregulated, while 174 were downregulated) were identified between high- and low-yield Yunshang black goats in the follicular phase (HF vs. LF); moreover, 361 DE circRNAs (136 were upregulated, while 225 were downregulated) were identified between high- and low-yield Yunshang black goats in the luteal phase (HL vs. LL). There were 65 DE circRNAs targeting 40 miRNAs in the HF vs. LF comparison and 46 DE circRNAs targeting 31 miRNAs in the HL vs. LL comparison. We identified chi_circ_0030920, chi_circ_0043017, chi_circ_0008353, chi_circ_0041580 and chi_circ_0016478 as the key circRNAs through functional enrichment analysis. The ceRNA network analysis showed that chi_circ_0031209 and chi_circ_0019448 might play an important role in reproduction by influencing the expression of PRLR in high- and low-yielding goats during the luteal phase, whereas chi_circ_0014542 regulates the expression of WNT5A during the follicular phase. Our study provided the overall expression profiles of circRNAs in the goat pituitary during the oestrus phase, which provides new insight into the mechanism of high yield goats, which can be helpful to guide goat breeding.